2019
DOI: 10.1116/1.5090860
|View full text |Cite
|
Sign up to set email alerts
|

Gas equilibration gas modulation refractometry for assessment of pressure with sub-ppm precision

Abstract: Gas Modulation Refractometry (GAMOR) has recently been developed to mitigate drifts in the length of the cavities in Dual-Fabry-Perot Cavity (DFPC) based refractometry. By performing repeated reference assessments with the measurement cavity being evacuated while the reference cavity is held at a constant pressure, the methodology can reduce the influence of the long-term drifts, allowing it to benefit from the high precision of DFPCbased refractometry at short time scales. A novel realization of GAMOR, referr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…It has previously been shown that for a DFPC refractometer the refractivity can be expressed as [4,6] 1 1 1 q , of the mode addressed in the empty measurement cavity when gas is let into the cavity.  is a normalized cavity deformation, defined as…”
Section: Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…It has previously been shown that for a DFPC refractometer the refractivity can be expressed as [4,6] 1 1 1 q , of the mode addressed in the empty measurement cavity when gas is let into the cavity.  is a normalized cavity deformation, defined as…”
Section: Theorymentioning
confidence: 99%
“…To reduce temperature overhearing, its reference junctions at the cavity are wound around the spacer a multitude of turns. Figure 4 provides a comparison between the Invar-based system and a similar system based on a Zerodur cavity [4]. Before the Ga fixed-point cell was implemented, for each cavity system, two measurement series were taken at dissimilar pressures; one when the system was evacuated, indicated in the form of Allan deviations in Fig.…”
Section: Temperature Stabilization and Assessmentmentioning
confidence: 99%
See 3 more Smart Citations